Role of macrophages in cardiorenal syndrome development in patients with myocardial infarction - M. A. Kercheva; V. V. Ryabov (Российский кардиологический журнал)
Cardiorenal syndrome (CRS) in patients with acute myocardial infarction (MI) underlies the development and progression of renal and heart failure. Along with the well-known mechanisms of CRS development based on reninangiotensin system activation, kidney-heart macrophage axis may be one of the key cellular components of CRS. Continuous sympathetic stimulation of collecting duct system cells under ischemia activates the macrophage link of the kidneys, which contributes to cardiac macrophages' polarization and leads to the development of adaptive myocardial hypertrophy and fibrosis. This review article summarizes current data on interaction of macrophages in the kidney-heart axis, which can be considered as the cellular basis for CRS development in patients with MI. The translation of experimental data on the participation of innate immune system on CRS model in humans will make it possible to find new ways to prevent and suppress acute kidney injury in patients with MI.